PSXV-13 The activity of thiol cathepsins in seminal plasma of stallions with different percentages of viable sperm after freezing-thawing. (8th October 2021) - Atroshchenko, Mikhail; Shitikova, Anna; Engalycheva, Mariya
Abstract: The aim of this work was to study the activity of cathepsins B, L and H in the seminal plasma of stallions with normal (>25%, n = 11) and low (< 25%, n = 13) percentage of viable sperm after freezing-thawing. Sperm of 24 Arabian stallions aged from 5 to 20 years (12.1 ± 4.8 years on average) was collected during the breeding season (February-May). The activity of cathepsins in spermoplasm was studied by the spectrofluorometric method (System 3 Scanning Spectrofluorometry, Optical technology devices, inc. Elmstord, New York, 10523) by Barrett&Kirschke. The viability of the sperm was determined after its freezing-thawing. Sperm smears were eosin stained and live:dead-ratio was examined using an Olympus BX41 phase contrast microscope (Olympus Corporation, Japan). The significance of differences in the studied groups was determined using the Mann-Whitney U-test. There were no significant differences in the activity of catepsins B and L in the spermoplasm of stallions with normal and low percentages of viable spermatozoa after freezing-thawing. It was found that in the group of stallions with a normal percentage of viable spermatozoa after freezing-thawing, the activity of cathepsin H in the spermoplasm was significantly higher than in the group with a low percentage of viable spermatozoa (P = 0.0219). Free radicals formed during freezing-thawing of sperm can damage cell membranes, leading to loss of sperm viability. Thiol cathepsins are involved in the degradation of oxidatively modified proteins and, apparently, it is cathepsin H that is most actively involved in this process in the sperm of stallions. We assume that the low activity of cathepsin H in the seminal plasma of stallions with a low percentage of viable spermatozoa indicates a high involvement of this enzyme in the protection of sperm membranes from oxidative damage. The research was supported by the Russian Science Foundation grant No. 20-16-00101.